2008
DOI: 10.1063/1.2825600
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the dominant hydration structures among the ionic species in aqueous solution: Novel quantum mechanics/molecular mechanics simulations combined with the theory of energy representation

Abstract: In the present work, we have performed quantum chemical calculations to determine preferable species among the ionic complexes that are present in ambient water due to the autodissociation of water molecule. First, we have formulated the relative population of the hydrated complexes with respect to the bare ion (H(3)O(+) or OH(-)) in terms of the solvation free energies of the relevant molecules. The solvation free energies for various ionic species (H(3)O(+), H(5)O(2) (+), H(7)O(3) (+), H(9)O(4) (+) or OH(-),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…(8) were fully examined in the various applications both in the QM/MM and pure classical simulations. 6,[29][30][31][32][33] We refer readers to the previous works for theoretical details about formulation of the free energy μ. 24 Here, we address the conventional approach to compute the many-body contribution δμ in Eq.…”
Section: A Qm/mm-er Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…(8) were fully examined in the various applications both in the QM/MM and pure classical simulations. 6,[29][30][31][32][33] We refer readers to the previous works for theoretical details about formulation of the free energy μ. 24 Here, we address the conventional approach to compute the many-body contribution δμ in Eq.…”
Section: A Qm/mm-er Approachmentioning
confidence: 99%
“…With the QM/MM-ER method, furthermore, there is no need to reduce the electron density of the solute to a set of point charges, and hence the spatially diffuse nature of electronic distribution is straightforwardly handled irrespective of the levels of theory in QM description. [29][30][31][32][33][34] The many-body effect of the solute-solvent interaction, that is inherent with the electron density fluctuation in solution, can also be addressed. 24,29,34 The drawback of the method is that it utilizes an approximate functional, though the error due to the functional was observed to be not larger than the error due to the use of force field.…”
Section: Introductionmentioning
confidence: 99%
“…(9) were examined by various applications both in the QM/MM and classical simulations. [31][32][33][34][35][36][37] We refer the readers to the previous works 19 for theoretical details about formulation of the free energy μ.…”
Section: A the Qm/mm-er Methodsmentioning
confidence: 99%
“…In the conventional theory of solutions, 10 the spatial distribution of the solvent molecules around the solute serves as a fundamental variable to evaluate the solvation free energy. In previous papers, [19][20][21][22][23][24][25] we performed QM/ MM-ER simulations for various chemical events in aqueous solutions to test the accuracy and efficiency of the method and found that our approach is quite adequate to compute free energy change for reactions in solution. 17,18 The advantage to combine the theory of energy representation with the QM/MM method is obvious.…”
Section: Introductionmentioning
confidence: 97%